ANALISA KERJA BLOWER PADA ALAT VENTILATOR - Putri Rizky Octaria Amazihono; Siti Rahmah (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Ventilator is a mechanical aid that functions to provide breathing assistance so that patients breathe easier. this study aims to determine how the blower works in mixing oxygen and what is the rotational speed of the blower when mixing. This research was conducted by the integrated laboratory of USM-I. The research method used was descriptive with the from of quantitative survey implementation. Which aims to analyze the working principle of the blower on the ventolator. This research was conducted using a Hamilton C2 ventilator. in the blower flow measurement is done from the preassure setting points 5, 15, 25, 35, 55. The results of this study indicate that the blower works welol on the ventilator and the measurement results of each blower flow value reading does not exceed the predetermined standard limit of +-10%.